Pengaruh Upaya Promosi Kesehatan, Perilaku Kesehatan Masyarakat, Dan Pencegahan Stunting Terhadap Terjadinya Kasus Stunting Di Kelurahan Lokus Stunting Kota Bandung - Nursulistya Murti (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2022)
Background : Toddler stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time which is marked by a child's height being shorter than the standard for children his age. Stunting children face a greater risk of growing up to become adults who are less educated, poorer, less healthy and more vulnerable to non-communicable diseases. Short children are a predictor of poor quality of human resources, which in turn reduces the productive ability of a nation in the future. The high prevalence of stunting is a problem that can threaten children's health. Objective: to see the relationship between health promotion factors, public health behavior, and stunting prevention on the occurrence of stunting cases Methods: This type of research is observational with survey methods and cross sectional approach. The research instrument used a questionnaire on 300 mothers of children under five who had stunted toddlers in the stunting locus sub-district, Bandung City. Primary and secondary data were processed and analyzed quantitatively using univariate, bivariate and multivariate methods, using regression analysis, the significance of which was determined by the p value < 0.05. Results: There is a significant relationship between health promotion (p-value = 0.267), health behavior (p-value = 0.272) and stunting prevention efforts (p-value = 0.352) on stunting incident. Conclusion: Health promotion, public health behavior and stunting prevention efforts are related to stunting, so it is necessary to carry out innovations and continuity of health promotion, both in methods, media and extension language that can inspire, understand and accurately capture the meaning of the community, so that the community ultimately feel the benefits and importance of changing bad health behaviors and ultimately participate actively in stunting prevention efforts, so that the stunting target below 20% can be achieved. Keywords: stunting, health promotion, public health behavior, stunting prevention efforts, stunting locus.